Prevalence and treatment of cardiovascular risk factors in outpatients with atherothrombosis in the Middle East. Issue 1 (22nd August 2011) - Alsheikh-Ali, Alawi A; Al-Mahmeed, Wael A; Porath, Avi; Khalil, Ismail; Mahmoud, Hisham; Bhatt, Deepak L; Steg, P Gabriel
Abstract : Objective: To characterise the risk-factor profile and treatment gaps among patients with, or at risk for, cardiovascular disease in the Middle East. Design: Secondary analysis of a prospective observational study. Setting: International multicentre study (Reduction of Atherothrombosis for Continued Health). Patients: Stable outpatients with established cardiovascular disease or at least three risk factors for atherothrombosis. The present analysis was based on 840 patients from the Middle East. Intervention: Observational study without a study-specific intervention. Main outcome measures: A treatment gap was defined as at least one of the following: current cigarette smoking, total cholesterol ≥200 mg/dl, serum glucose ≥126 mg/dl or blood pressure of ≥140/90. Results: The majority of Middle Eastern patients had hypertension (80.2%), more than half had a history of diabetes mellitus (52.3%), and a third had hypercholesterolaemia (34.1%). There was a high prevalence of obesity (38.6%), and nearly half the patients were former or current smokers (46%). β-Blockers and angiotensin-converting enzyme inhibitors were the most commonly prescribed antihypertensives (61.1% and 57.5%, respectively). Antiplatelet therapy (most commonly aspirin) and lipid-lowering drugs (most commonly a statin) were used in most patients (90.7% and 85.2%, respectively). Three-quarters of the participants (75.6%) had at least one uncontrolled risk factor. Conclusion: Patients with atherothrombosis in the Middle East have a high prevalence of risk factors including alarming rates of diabetes mellitus and obesity. At least one risk factor is uncontrolled in the majority of patients, presenting a pressing need for improving the care of such patients in the Middle East.